The Control of the The Exemption Clauses - Gual Acosta, José Manuel (Universidad Santo Tomás, Bogotá-Colombia, 2016)
The exemption clauses of liability have emerged as one of the main problems of modern law of contracts.In spite of its routine use compared with some countries have used a fragmented and dispersed systemas in the Colombian case against others who have a systematic regime.Seeks a balanced legal business from the perspective of the obligations and duties arising under thecontract for the parties. We notes with concern that the classics on the formation of the contract to dateare inadequate to protect the weaker contracting party against the possibility that some clauses of thecontract by the membership will be unfair.Hence the concern to analyze the main problems that arise in the foreign law against unfair terms inorder to practise effective control over them. And as the law faces in the absence of a specific system ofcontrol over them.